Searching for a landing site. (Economist, 2019)
The article describes the condition of the Indian economy in 2019. The country's gross domestic product (GDP) growth dropped in the 12 months ending in September. India has suffered economic problems such as chronic inflation, high oil prices and an unsustainable current account deficit. The Reserve Bank of India has reduced interest rates in order to stabilize the economy.